Stressor, Abusive Supervision dan Tipe Kepribadian Terhadap Kelelahan Emosional - Astuti Jovitasari; . Miftahuddin (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
The purpose of this study was to see how the influence of stressors from customers, abusive supervision and personality types on emotional fatigue experienced by frontliner employees at the hotel (N = 150). Current study used quatitative method. The scale used in this study is Customer-related Social Stressors, Abusive Supervision, Big Five Inventory (BFI). The results of this study indicate that only three independent variables were stated to significantly affect employee emotional exhaustion. Where the three variables are customer expectations that are not appropriate, verbal aggression from customers and abusive supervision.